KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS BERDASARKAN GAYA BELAJAR SISWA - Laras Mawar Sari; Sutirna Sutirna; Dani Firmansyah (IKIP Siliwangi, 2023)
This research is motivated by one of the objectives of learning mathematics is so that students have the ability to understand mathematical concepts. However, the reality on the ground shows that students' ability to understand concepts is still low, so it requires a teacher's understanding of the factors that influence it, namely learning styles. This study aims to describe the ability to understand mathematical concepts in terms of learning styles. The approach used is descriptive qualitative. The research subjects were 3 students from 21 grade VII-A students of SMPN 3 Cikampek. Data was collected through learning style questionnaires, written tests, and interviews. This study's results indicate that students with different learning styles have different results in understanding concepts. Visual learning style students in general are quite capable of meeting indicator of ability to understand mathematical concepts that can meet 3 indicators, students of auditory learning style are generally said to be good or almost meet every indicator of ability to understand concepts that can meet 5 indicators, while kinesthetic learning style in general not good at fulfilling each indicator, which is only able to meet 2 indicators of the ability to understand mathematical concepts.